Tissue Factor and Homocysteine Levels in Ischemic Heart Disease Are Associated with Angiographically Documented Clinical Recurrences after Coronary Angioplasty - Marcucci, Rossella; Prisco, Domenico; Brunelli, Tamara; Pepe, Guglielmina; Gori, Anna Maria; Fedi, Sandra; Capanni, Monia; Simonetti, Ignazio; Federici, Giorgio; Pastore, Anna; Abbate, Rosanna; Gensini, Gian Franco (Thrombosis and Haemostasis, 2000)
Background In ischemic heart disease (IHD) patients high plasma levels of Tissue Factor (TF), the trigger of coagulation cascade, are present. Homocysteine (Hcy) is a risk factor for coronary artery disease, and several different pathophysiological mechanisms by which Hcy may play a role in thrombus formation have been postulated in “in vitro” studies. We investigated the “in vivo” role of Hcy in affecting plasma levels of TF, its inhibitor Tissue Factor Pathway Inhibitor (TFPI) and hypercoagulability. Methods and Results We investigated 119 IHD patients who underwent PTCA and compared them with 103 healthy subjects. TF, TFPI, Thrombin-Antithrombin complexes (TAT) and Hcy levels were significantly higher in the patients than in the controls. A positive correlation was found between Hcy and TF (r = 0.54; p < 0.0001), Hcy and TFPI (r = 0.26; p < 0.05) as well as Hcy and TAT (r = 0.33; p < 0.0001) levels. An inverse correlation existed between folate intake and Hcy levels (r = −0.28; p = 0.001). Hcy levels within the first quartile and in the highest quartile were associated with a lower (p < 0.001) and higher (p <0.0001) rate of clinical recurrences, respectively. Patients with TF values in the first quartile had a lower rate of angiographically documented clinical recurrences as compared to those in the fourth quartile (p < 0.01); those in the highest quartile of TF showed a higher rate of recurrences (p = 0.001). Multivariate analysis confirmed these results (first quartile of Hcy: OR 0.02, Cl 0.002–0.27; fourth quartile of Hcy: OR 36.5, Cl 3.6-365/first quartile of TF: OR 0.006, Cl 0.001–0.44; fourth quartile of TF: OR 16.4, Cl 3.0 – 90.0), also after adjustment for risk factors and Hcy and TF respectively. Conclusions In this study we show that TF, TFPI and TAT levels are correlated with Hcy plasma levels in IHD patients, providing evidence of an “in vivo” pathophysiological mechanism of hyperhomocysteinemia. The observed association between angiographically documented clinical recurrences and TF and Hcy values awaits confirmation in studies designated to evaluate this issue on a larger number of patients.
Keywords: Coronary disease; risk factors; coagulation; angioplasty